Compressors selection and sizing - Brown, Royce N
This practical reference provides in-depth information required to understand and properly estimate compressor capabilities and to select the proper designs. Engineers and students will gain a thorough understanding of compression principles, equipment, applications, selection, sizing, installation, and maintenance. The many examples clearly illustrate key aspects to help readers understand the "real world" of compressor technology.Compressors: Selection and Sizing, third edition is completely updated with new API standards.